SOLUSI TEKNOLOGI INFORMASI DAN MANAJEMEN PRODUK SEBAGAI UPAYA UNTUK MENINGKATKAN PERAN USAHA MIKRO KECIL DAN MENENGAH DI DESA SENDANG TIRTO BERBAH SLEMAN - sholeh, muhammad (Jurnal FTI, 2015)
The development of technology especially Information and Communication Technology (ICT) provides new opportunities to overcome some of the problems of SMEs. Although not a major problem, but the opportunities brought by ICT is very large, and based on conditions on the ground, indicate that the adoption of ICT by SMEs sector is still not up compared with large companies. Utilization of ICT can also be used for the promotion of SMEs. Likewise, in the process of cashew production and the processes of packaging still using simple tools so that productivity can not be optimized.In the implementation of this IbM, the activities are divided into three. First: Activities are oriented towards activities stripping and processed cashew nuts. In stripping cashew ergonomic equipment required in order to process cashew stripping can be done easily and activities associated with the use of technology to processed of packaging. Second: the activities related to the promotion process Sendang Tirto by optimizing information technology. These activities include building a village website Sendang Tirto, training for administrators so that the filling process and the renewal of the website can be continuously carried out.Â  Â Keywords: IbM, SMEs, Cashew, Sendang Tirto, ICT